Isolation and characterization of aerobic actinomycetes with probiotic properties in Nile tilapia - Jirayut Euanorasetr&, Varissara Chotboonprasit&, Wacharaporn Ngoennamchok&, Sutassa Thongprathueang&, Archiraya Promprateep&, Suppakit Taweesaga&, Pongsan Chatsangjaroen&, Bungonsiri Intra& (Journal of Applied Pharmaceutical Science, 2020)
This study scoped the isolation of aerobic actinomycetes with probiotic properties against bacterial pathogens in Nile tilapia. Eleven rhizosphere soil samples were collected from the agricultural sites in three provinces (Chanthaburi, Nan, and Chachoengsao) of Thailand. A total of 157 actinomycete-like colonies were successfully isolated. The antibacterial testing against four tested bacteria (Streptococcus agalactiae 2809, Aeromonas jandaei 1929, Aeromonas veronii 1930, and Edwardsiella ictaluri 2234) was carried out by a modified cross-streaked method. The results showed that 108 strains possessed antibacterial activity against at least one of the bacterial pathogens. Seventeen active isolates were identified in the actinomycetes by the analysis of the partial 16S ribosomal rRNA gene, and the phylogenetic relationships of the isolates and their closely related strains were confirmed by the neighbor-joining method. Isolates LNW002 and YNW004 survived in the liquid cultivation with International Streptomyces Project 2 at pH 2 and the presence of 0.3% bile salt for 2 hours, which mimics the gastric acidity and bile salt in the gastrointestinal tract of Nile tilapia in vitro. In conclusion, these strains might be further investigated for their efficacy as probiotics in Nile tilapia. This study is the first to report on anti-E. ictaluri activity in streptomycetes.
Keywords: Actinomycetes, antibacterial activity, probiotics, bacterial pathogens, Nile tilapia.